Suspected natural lysosomal storage disease from ingestion of pink morning glory (Ipomoea carnea) in goats in northern Argentina - Ríos, Elvio Eduardo (2015)
Fil: Ríos, Elvio Eduardo. Universidad Nacional del Nordeste. Facultad de Ciencias Vetrinarias; Argentina.